Labor quality and growth accounting the Philippines - Patalinghug, Epictetus E. (The Philippine Review of Business and Economics, 1984)
In recent years studies in human capital have been readily absorbed into the larger body of economic knowledge. However, there is a scarcity of studies on the value of education between sectors. This paper is an attempt to apply the growth accounting framework so as to determine the significance of education in manufacturing and agriculture sectors of the Philippine economy. A weighted education per man index (where the weights are earnings by years of schooling) was employed in measuring human capital input and incorporating it into the production function. Empirical results indicate that education's contribution to Philippine growth rate between 1960 and 1982 is only 17.34 per cent; capital is the dominant factor which accounts for 48.26 per cent of the growth rate during the period. It seems that the role of education in improving the quality of the Philippine labor force does not appear to be significantly substantial; on the contrary, the crucial role of physical capital (rather than human capital) in Philippine economic growth is supported by the evidence.